Synthesis and Conductivity Measurement of Polyacrylamide in Nano State - Chetri, P.; Sen Sarma, N.; Pal, A.R.; Bailung, H.; Chutia, J.; Dass, N.N. (Asian Journal of Chemistry, 2010)
Polyacrylamide was synthesized from its monomer by plasma polymerization technique. The polymer so formed is in nano state and was confirmed by IR, UV and SEM techniques. Conductivities were determined from 30 to 200 ºC with a frequency ranges from 42 Hz to 1 MHz in solid state. Observation indicates that the nano state showed better ionic conductivity than of the bulky one. SEM analysis indicates that the particle size of polyacrylamide prepared by plasma polymerization is within the range 60 to 100 nm. A possible mechanism for the formation of polyacrylamide by plasma technique is also explained.